Cross-cultural adaptation, reliability, and validation of the Taiwan-Chinese version of Cumberland Ankle Instability Tool. Issue 5 (27th February 2022) - Lin, Chiao-I; Mayer, Frank; Wippert, Pia-Maria
Abstract: Purpose: To cross-cultural translate the Cumberland Ankle Instability Tool (CAIT) to Taiwan-Chinese version (CAIT-TW), and to evaluate the validity, reliability and cutoff score of CAIT-TW for Taiwan-Chinese athletic population. Materials and methods: The English version of CAIT was translated to CAIT-TW based on a guideline of cross-cultural adaptation. 77 and 58 Taiwanese collegial athletes with and without chronic ankle instability filled out CAIT-TW, Taiwan-Chinese version of Lower Extremity Functional Score (LEFS-TW) and Numeric Rating Scale (NRS). The construct validity, test-retest reliability, internal consistency and cutoff score of CAIT-TW were evaluated. Results: In construct validity, the Spearman's correlation coefficients were moderate (CAIT-TW vs LEFS-TW: Rho = 0.39, p  < 0.001) and strong (CAIT-TW vs NRS: Rho= 0.76, p  < 0.001). The test retest reliability was excellent (ICC2.1 = 0.91, 95% confidential interval = 0.87–0.94, p  < 0.001) with a good internal consistency (Cronbach's α: 0.87). Receiver operating characteristic curve showed a cutoff score of 21.5 (Youden index: 0.73, sensitivity: 0.87, specificity 0.85). Conclusions: The CAIT-TW is a valid and reliable tool to differentiate between stable and instable ankles in athletes and may further apply for research or daily practice in Taiwan. Implications for rehabilitation: For athletes, chronic ankle instability is prevalent and causes negative sequela, such as lowered quality of daily life, affected functional performance, and may cause post traumatic osteoarthritis. The psychometric properties of the Taiwan-Chinese version of the Cumberland Ankle Instability Tool showed moderate to strong construct validity, excellent test retest reliability, a good internal consistency and a cutoff score of 21.5. The validity and reliability of the Taiwan-Chinese version of the Cumberland Ankle Instability Tool are to enable clinicians to evaluate and manage ankle instability in Taiwanese who speaks Mandarin Chinese.